2018
DOI: 10.1021/acs.chemmater.7b05278
|View full text |Cite
|
Sign up to set email alerts
|

Structural Disorder and Coherence across the Phase Transitions of Lead-Free Piezoelectric Bi0.5K0.5TiO3

Abstract: Relaxor ferroelectrics exhibit superior properties for converting mechanical energy into electrical, and vice versa, but the structural disorder hampers an understanding of structureproperty relationships, and impedes rational design of new, lead-free materials. Bi0.5K0.5TiO3 (BKT) is a prototypical lead-free relaxor ferroelectric, but the microscopic origins of polarization, nature of the ferroelectric transition (TC) and structural changes across the tetragonal to pseudo-cubic transition (T2) are poorly unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 61 publications
6
28
0
Order By: Relevance
“…As such, it has attracted attention as a component in piezoelectric solid solutions, several of which yield technologically relevant properties [11][12]. Despite multiple studies [13][14][15][16][17][18][19][20][21], the details of the KBT structure and the exact nature of its ferroelectric cubic↔tetragonal phase transition remain uncertain. Analysis of the literature reveals two different results.…”
Section: Introductionmentioning
confidence: 99%
“…As such, it has attracted attention as a component in piezoelectric solid solutions, several of which yield technologically relevant properties [11][12]. Despite multiple studies [13][14][15][16][17][18][19][20][21], the details of the KBT structure and the exact nature of its ferroelectric cubic↔tetragonal phase transition remain uncertain. Analysis of the literature reveals two different results.…”
Section: Introductionmentioning
confidence: 99%
“…6(c), compared with the cell volume of pure BKT prepared by us, the cell volume of BKMS is closer to the theoretical value of pure BKT (61.48 ¡). 24) And the cell volume of BKMS presents an obvious shrinkage at low and high sintering temperature regions. It is suggested that the cell shrinkage may be the result of the sintering ability of the BKMS ceramics.…”
Section: Resultsmentioning
confidence: 99%
“…the same row) in Table 1, it can be seen that there are small differences. These are most noticeable in the LaB 6 and Ni samples, which is a known artefact (Jiang et al, 2018;Hong et al, 2016). However, this difference decreases after the correction is applied, which is most notable for CeO 2 .…”
Section: Figurementioning
confidence: 93%
“…Total scattering and pair distribution function (PDF) analysis has served as an excellent tool for understanding the local structures of disordered materials, offering new insights that traditional powder diffraction methods have been unable to achieve (Hou et al, 2018;Keen & Goodwin, 2015;Young & Goodwin, 2011;Proffen & Kim, 2009;Petkov, 2008;Billinge, 2008Billinge, , 2019Egami, 2007). This field has been rapidly evolving with the developments in computing power, brighter radiation sources and detector efficiencies, allowing more complex experiments and modelling to be achieved (Eremenko et al, 2017;Jiang et al, 2018;Jensen et al, 2012Jensen et al, , 2015Usher et al, 2015;Hu et al, 2013;Roelsgaard et al, 2019;Pramanick et al, 2018).…”
Section: Introductionmentioning
confidence: 99%